2017
DOI: 10.1177/0263617417701744
|View full text |Cite
|
Sign up to set email alerts
|

Epoxidation of cyclopentene by a low cost and environmentally friendly bicarbonate/peroxide/manganese system

Abstract: The system hydrogen peroxide/sodium bicarbonate/manganese sulfate was used for the first time to epoxidize cyclopentene. Effects of parameters such as type and amount of solvent, ratio of hydrogen peroxide and manganese sulfate to cyclopentene, presence of additives, and reaction time and temperature on the selectivity to cyclopentene oxide were evaluated. Gas chromatography was used to quantify residual cyclopentene and produced cyclopentene oxide using the internal standard method. Type and amount of solvent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Higher temperature and molar ratio H 2 O 2 /CPE under heterogenous conditions were not tested since under homogeneous conditions for the epoxidation of CPE in the system Mn(II)/ DMF/NaHCO 3 /H 2 O 2 increasing temperature and molar ratio H 2 O 2 /CPE decreased the selectivity of the epoxidation. [24] The presence of a dark precipitate after 30 min of reaction, was reported in the homogenous epoxidation of CPE. [24] This dark precipitate could be related either to the precursors or to birnessite (OL-1) since manganese sulfate in basic media and under oxidant conditions has been used to synthesize OMS-2, the transformation reported was from Mn 2 + to Mn 3 + rich feitknechtite to birnessite (OL-1) and after calcination to OMS-2.…”
Section: Chemistryselectmentioning
confidence: 93%
See 2 more Smart Citations
“…Higher temperature and molar ratio H 2 O 2 /CPE under heterogenous conditions were not tested since under homogeneous conditions for the epoxidation of CPE in the system Mn(II)/ DMF/NaHCO 3 /H 2 O 2 increasing temperature and molar ratio H 2 O 2 /CPE decreased the selectivity of the epoxidation. [24] The presence of a dark precipitate after 30 min of reaction, was reported in the homogenous epoxidation of CPE. [24] This dark precipitate could be related either to the precursors or to birnessite (OL-1) since manganese sulfate in basic media and under oxidant conditions has been used to synthesize OMS-2, the transformation reported was from Mn 2 + to Mn 3 + rich feitknechtite to birnessite (OL-1) and after calcination to OMS-2.…”
Section: Chemistryselectmentioning
confidence: 93%
“…[24] The presence of a dark precipitate after 30 min of reaction, was reported in the homogenous epoxidation of CPE. [24] This dark precipitate could be related either to the precursors or to birnessite (OL-1) since manganese sulfate in basic media and under oxidant conditions has been used to synthesize OMS-2, the transformation reported was from Mn 2 + to Mn 3 + rich feitknechtite to birnessite (OL-1) and after calcination to OMS-2. [25,45,46] The active sites required for the epoxidation of CPE are formed in situ during the homogenous process and could be Scheme 1.…”
Section: Chemistryselectmentioning
confidence: 93%
See 1 more Smart Citation
“…Carbonates have often been used as activators for oxidation reactions with hydrogen peroxide, including epoxidation reactions [ 20 , 21 , 22 , 23 , 24 ]. It has been reported that percarbonate is involved in manganese-catalyzed alkene epoxidation reactions using hydrogen peroxide in carbonate or bicarbonate aqueous solutions [ 20 , 21 , 24 , 25 , 26 ]. Burgess and co-workers proposed the involvement of manganese η 2 -peroxycarbonate complexes to facilitate the cleavage of the O–O bonds of percarbonate ions.…”
Section: Introductionmentioning
confidence: 99%